INNOVATION IN DA'WAH COMMUNICATION IN ISLAMIC EDUCATION IN THE ERA OF SOCIETY 5.0 - Surya Eka Priyatna; Wahyudin; Saifuddin Sabda (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2025)
The Industry 5.0 era signifies a paradigm shift in Islamic education communication, moving from knowledge transmission toward human-centered, value-driven, and meaning-oriented interaction. This transformation poses critical challenges for dakwah communication, particularly in engaging digitally immersed generations shaped by intelligent technologies and algorithmic media ecosystems. This article aims to examine how innovative dakwah communication in Islamic education can be developed without compromising spiritual integrity and scholarly authority. Employing a qualitative approach through critical literature review and conceptual-reflective analysis, this study synthesizes contemporary digital dakwah practices to identify key patterns, challenges, and opportunities. The findings indicate that technological integration, such as social media, artificial intelligence, and adaptive learning, becomes effective only when embedded within empathetic, participatory, and spiritually grounded communication frameworks. This study introduces the concept of a spiritual-digital generation to reconceptualize contemporary dakwah audiences and proposes a human-centered religious communication model aligned with the principles of Education 5.0. The study contributes theoretically and practically by offering a nuanced framework for sustainable and ethical Islamic dakwah communication in the Industry 5.0 context.